Identifying the descriptor governing NO oxidation on mullite Sm(Y, Tb, Gd, Lu)Mn2O5 for diesel exhaust cleaning. Issue 11 (21st January 2016) - Li, Hao-Bo; Wang, Wei-Hua; Qian, Xinyu; Cheng, Yahui; Xie, Xinjian; Liu, Jieyu; Sun, Shuhui; Zhou, Jigang; Hu, Yongfeng; Xu, Jianping; Li, Lan; Zhang, Yan; et al.
Abstract : Mn-based oxides Sm(Y, Tb, Gd, Lu)Mn2 O5 are synthesized to identify a general descriptor that governs the catalytic performance in NO oxidation. Abstract : The current fast selective catalytic reduction (fast-SCR) technology shows effectiveness in converting diesel engine generated nitrogen oxides (NO x ) to environmentally benign nitrogen (N2 ) with the aid of the precious metal catalyst platinum. Driven by the previous finding of the low-cost mullite's great superiority over Pt in terms of NO oxidation, a series of Mn-based oxides Sm(Y, Tb, Gd, Lu)Mn2 O5 are synthesized to identify a general descriptor that governs the catalytic performance. Utilizing soft X-ray absorption characterization and molecular orbital theory, here, we show that the catalytic activity difference presents little dependence on the 3d electron occupancy when the A site element is varied (Sm, Tb, Y, Gd, Lu). Instead, strong p–d hybridization between lattice O and octahedral Mn leads to weak bonding strength between external O* and pyramid Mn and essentially increases the catalytic activity for converting NO to NO2 .